Risk Attitudes and Household Migration Decisions - Christian Dustmann; Francesco Fasani; Xin Meng; Luigi Minale (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
This paper analyses the relation between individual migrations and the risk attitudes of other household members when migration is a household decision. We develop a simple model that implies that which members migrate depends on the distribution of risk attitudes among all household members, and that the risk diversification gain to other household members may induce migrations that would not take place in an individual framework. Using unique data for China on risk attitudes of internal (rural-urban) migrants and the families left behind, we empirically test three key implications of the model: (i) that conditional on migration gains, less risk averse individuals are more likely to migrate; (ii) that within households, the least risk averse individual is more likely to emigrate; and (iii) that across households, the most risk averse households are more likely to send migrants as long as they have at least one family member with sufficiently low risk version. Our results not only provide strong evidence that migration decisions are taken on a household level but also that the distribution of risk attitudes within the household affects whether a migration takes place and who will emigrate.
Keywords: J61; O15; R23; D81; 330; risk aversion; internal migration; household decisions